2020
DOI: 10.1002/celc.202000405
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic Ag/Pd Alloy Nanostructure Arrays for Electrochemical CO2 Reduction

Abstract: Electrochemical reduction of CO2 to value‐added chemicals is a promising strategy for the utilization of excess CO2. But, such reaction suffers from poor efficiency due to insufficient selectivity of electrocatalysts. Aimed at developing highly efficient electrocatalysts, dendritic Ag/Pd alloys with different compositions were synthesized through a simple galvanic replacement reaction. We found that the Ag/Pd alloy with an atomic ratio of 70 % Ag and 30 % Pd can selectively convert CO2 to CO with a maximum far… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Generally speaking, both doping and alloying can adjust the electronic structure of metals, thus effectively promoting the reaction kinetics [9,21] . X‐ray photoelectron spectroscopy (XPS) analysis further explores the chemical states of each component in the nanocomposite and the shift in electron state around Ag and Sn.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally speaking, both doping and alloying can adjust the electronic structure of metals, thus effectively promoting the reaction kinetics [9,21] . X‐ray photoelectron spectroscopy (XPS) analysis further explores the chemical states of each component in the nanocomposite and the shift in electron state around Ag and Sn.…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, a lot of efforts have been devoted to modulating Ag‐based catalysts’ size, morphology and structure, aiming at boosting their electrocatalytic performance [9–13] . Especially the formation of defects in nano Ag materials has been reported to obtain high selectivity toward C1 production, which is due to the destruction of the local spatial symmetry and ordered arrangement around the crystal from the defects.…”
Section: Introductionmentioning
confidence: 99%
“…The surface composed of accumulated nano-spherical Cu 2 O was generated after growing the Cu 2 O shell, as compared to the pristine ZnO core. This coarse structure generally had a larger external surface area and could provide more active sites [30,31]. The Cu 2 O sample showed a similar morphology.…”
Section: Xzno@ycu 2 O Catalystmentioning
confidence: 96%
“…[6d,10] For instance, Han et al [11] have reported an enhancement of CO production even at lower potentials by creating a Pd and ceria interface. A recent study by Zhang and co-workers [12] stressed the benefit of forming AgÀ Pd alloy dendritic nanostructure to enhance CO production. They achieved 98.6 % FE for CO at À 0.80 V vs RHE with dendrites containing 70.0 % Ag and 30.0 % Pd.…”
Section: Introductionmentioning
confidence: 99%